Electrochemical Evaluation of Fluorinated MnO2 for Supercapacitor Application - Siti Nur Najwa, Mohd Yusof; Nurul Khairiyyah, Mohd Zain; Izan Izwan, Misnon; Rajan, Jose (EDP Sciences, 2018)
Supercapacitors (SCs) functioning as alternative energy storage is useful in most electronic devices, renewable energy system and hybrid vehicles that have high demand in these days. Excellent electrochemical performance, environment friendliness and low cost material are needed to fulfil the energy demand by most developed country. In this study, fluorination treatment on manganese oxide (MnO2) is considered as an effective way to develop better energy storage due to fluorine electronegativity and reactivity when correlate with other element. Hydrothermal method is used to synthesis MnO2 (MnO2 and MnO2) and the effect of fluorination (FMnO2 and FMnO2) on MnO2 surfaces is investigated on the charge storage ability. The crystallinity and functional groups of the samples was confirmed by the X-ray diffractogram and fourier transforms infrared spectroscopy (FTIR). The cyclic voltammetry (CV) and galvanostatic charging–discharging (CDC) analysis in 0.5 M K2SO4 electrolyte shows that F--MnO2 gives the highest Cs value of 184 F g-1 at scan rate of 5 mV s-1 and 66 F g-1 at current density of 0.3 A g-1. The electrochemical impedance spectroscopy shows that the FMnO2 has the lowest electrode resistances and charge transfer resistance which contributes to high Cs and the high conductivity of electrode.